A Study on Blood Lactate Removal Among the Football Players - Rupali Katoch; Krishnendu Dhar (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The purpose of the study was to compare the blood lactate removal between active and passive recovery modes. Ten (10) under-17 national-level football players were purposively selected to fulfill the study. Participants performed a treadmill run at 90% intensity followed by either a 5-minute active or passive recovery mode. Active recovery resulted in significantly greater lactate reduction after 5 minutes (4.32 ± 2.1 mmol/L decrease) compared to passive rest (2.27 ± 1.11 mmol/L). The rapid early clearance with activity indicates better blood circulation and lactate metabolism. In addition, the difference was insignificant after 10 minutes of facilitation of both recovery modes. This study concluded that active recovery provides transient metabolic benefits optimizing lactate reduction rate for a short period. However, more research needed on durations and subsequent performance impacts will reveal ideal practical applications for intermittent, high-intensity sports.